Efektivitas Media Poster Dan Media Video Animasi Terhadap Tingkat Pengetahuan Remaja Mengenai Hipertensi - Fuji Sri Rahayu; Ratih Kurniasari (Jurnal Kesehatan, 2022)
Hypertension is a condition in which systolic blood pressure increases by more than 140 mmHg or diastolic blood pressure is more than 90 mmHg. One of the efforts made to improve adolescents' understanding of hypertension is by education through the media. The purpose of this study is to find out the influence of providing education using poster media and animated video media on the level of adolescent knowledge related to hypertension. This type of quasi-experimental research with pretest-posttest research design. The statistical tests used are the Paired Sample T-Test and the Wilcoxon Test. The results of the paired sample t-test showed that the poster media value of p value 0.000 (p<0.05) had a significant influence on adolescent knowledge levels related to hypertension. The results of the Wilcoxon test showed that animated video media values of p value 0.000 (p<0.05) had a significant influence on adolescent knowledge levels related to hypertension. It can be concluded that Poster Media and Animated Video Media are effective in increasing adolescent knowledge related to hypertension and the two media have the same influence in increasing adolescent knowledge related to hypertension.